Proteomic and ubiquitinome analysis reveal that microgravity affects glucose metabolism of mouse hearts by remodeling non-degradative ubiquitination. - Xin Zhang; Xuemei Zhou; Zhiwei Tu; Lihua Qiang; Zhe Lu; Yuping Xie; Cui Hua Liu; Lingqiang Zhang; Yesheng Fu (PLoS ONE)
Long-term exposure to a microgravity environment leads to structural and functional changes in hearts of astronauts. Although several studies have reported mechanisms of cardiac damage under microgravity conditions, comprehensive research on changes at the protein level in these hearts is still lacking. In this study, proteomic analysis of microgravity-exposed hearts identified 156 differentially expressed proteins, and ubiquitinomic analysis of these hearts identified 169 proteins with differential ubiquitination modifications. Integrated ubiquitinomic and proteomic analysis revealed that differential proteomic changes caused by transcription affect the immune response in microgravity-exposed hearts. Additionally, changes in ubiquitination modifications under microgravity conditions excessively activated certain kinases, such as hexokinase and phosphofructokinase, leading to cardiac metabolic disorders. These findings provide new insights into the mechanisms of cardiac damage under microgravity conditions.